2019
DOI: 10.18051/jbiomedkes.2019.v2.15-19
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi antara kadar procalcitonin dengan serum transaminase pada pasien sepsis: sebuah studi pendahuluan

Abstract: LATAR BELAKANGSepsis merupakan suatu respon sistemik terhadap infeksi. Sepsis masih merupakan penyebab kematian utama pada kasus kritis di berbagai penjuru dunia. Central of Disease Control (CDC) pada tahun 2016 mencatat sedikitnya 1.7 juta orang dewasa mengalami sepsis per tahunnya, dengan angka kematian mencapai rata rata 270.000 orang per tahun di Ameriksa Serikat. Procalcitonin (PCT) merupakan pemeriksaan baku emas pada kasus sepsis bakterial. Kejadian sepsis akan menyebabkan terjadinya gagal multi-organ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A previous study showed that inflammation in thalassemia patients can occur due to iron accumulation 22 . The onset of inflammation can also lead to liver dysfunction 23 . Ferritin levels exceeding 1,000 ng/mL in thalassemia patients due to iron overload cause organ dysfunction, appearing first in the liver 24 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that inflammation in thalassemia patients can occur due to iron accumulation 22 . The onset of inflammation can also lead to liver dysfunction 23 . Ferritin levels exceeding 1,000 ng/mL in thalassemia patients due to iron overload cause organ dysfunction, appearing first in the liver 24 .…”
Section: Introductionmentioning
confidence: 99%